Pengaruh Motivasi Terhadap Kinerja Pegawai Pada Dinas Komunikasi Dan Informatika Kabupaten Bima - Adeina Sri Nining; Jaenab Jaenab; Wulandari Wulandari (Universitas 45 Surabaya, 2023)
The demand for high employee performance has actually become part of a company, because a successful organization cannot be separated from the performance of the employees who work in that organization, making human assets that can create ideal implementation so that organizational goals will be achieved. Discussing employee performance cannot be separated from the factors that can influence a person's performance (Saputra, 2023). Considering that employee performance problems are very complex, parties involved in the company must be careful in observing existing resources. Employee performance is greatly influenced and depends on the quality and competitive ability of the human resources they have. An employee's performance is an individual matter, because each employee certainly has a different level of ability or expertise in carrying out their duties. Management can measure employees based on the performance of each employee (Adha, 2019). Work motivation and performance are parts that are interrelated with each other, increasing work motivation will influence increased performance and vice versa. Work motivation is a stimulus or stimulus for each employee to work in carrying out their duties. With good motivation, employees will feel happy and enthusiastic at work, resulting in significant development and growth in the organization. According to Maruli (2020), work motivation is everything that arises from a person's desires, by generating passion and desires within a person that can influence, direct and maintain behavior to achieve goals or desires that are in accordance with the scope of work. Supported by Ferdinatus (2020)